Adopting Michael Fullan’s Framework to Illuminate Islamic Education Teachers’ Struggles for the Enactment of Government-Prescribed Curriculum - Zainal Abidin; Nani Endri Santi; Lathifah Hanum (Edukasia Islamika : Jurnal Pendidikan Islam, 2020)
The present study aims to elucidate the struggles of Islamic education teachers for the enactment of the 2013 Curriculum, the national curriculum, in Aceh, Indonesia adopting Michael Fullan’s framework. Grounded in a case study approach, data were garnered through in-depth interviews situated in senior secondary schools. Twelve urban and rural Islamic education teachers were recruited to participate in this case study. The study was conducted in six regencies. Study findings demonstrate that urban Islamic education teachers applied the objectives, materials, methods, and learning assessments in accordance with the government-prescribed curriculum. Rural Islamic education teachers did not receive sufficient facilities to enact the national curriculum. This study exposes that Fullan’s framework could be adapted to illuminate the best practice and understanding of Islamic education teachers in implementing the national curriculum, i.e.: building leadership communication, creating a conducive atmosphere and overcoming emerging problems, organizing teacher discussion forums, determining professional goals, building the capacity of educators, strengthening positive evaluation, and strengthening financial management. The study also indicates that support from the school and government is pivotal to require for Islamic education teachers to guarantee the quality of education in supporting the enactment of the government-mandated curriculum. Curriculum development, therefore, needs to be communicated to Islamic education teachers regarding the sustainable development of teacher competencies, e.g. organizing seminars, workshops, and developing learning materials